Cancer risk associated single nucleotide polymorphisms of mitochondrial D-loop and 8-hydroxy-2'-deoxyguanosine levels in gastric cancer. Issue 2 (4th March 2017) - Wang, Yingnan; Zhao, Yufei; Zhao, Yue; Luo, Xiaoxu; Guo, Zhanjun; Zhang, Ruixing
ABSTRACT: The accumulation of mutations and single nucleotide polymorphisms (SNPs) in the displacement loop (D-loop) of mitochondrial DNA (mtDNA) is related to gastric carcinogenesis. To evaluate the potential relationships between DNA damage and D-loop SNPs, we measured the 8-hydroxy-2'-deoxyguanosine (8-OHdG) levels in the gastric cancer tissue by immmunostaining. Our data showed that the gastric cancer susceptibility SNP of 16519C was associated with higher 8-OHdG levels. Taken together, the cancer-risk associated D-loop SNPs might initiate carcinogenesis through increasing oxidative damage.